2022
DOI: 10.1111/omi.12361
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use enriches periodontal pathogens

Abstract: The effect of electronic cigarette (e-cigarette) smoking, especially its long-term impact on oral health, is poorly understood. Here, we conducted a longitudinal clinical study with two study visits, 6 months apart, to investigate the effect of e-cigarette use on the bacterial community structure in the saliva of 101 periodontitis patients. Our data demonstrated that e-cigarette use altered the oral microbiome in periodontitis patients, enriching members of the Filifactor, Treponema, and Fusobacterium taxa. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…While tobacco smokers reported changes in taste, e-cigarette users did not. Reporting gingival inflammation with use of tobacco and e-cigarettes agrees with prior studies showing this association [ 29 , 30 , 31 , 32 , 33 ]. Smoking masks gingival inflammation by reducing gingival bleeding due to the vaso-constrictive effects of nicotine and lower hemorrhagic responsiveness in smokers [ 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…While tobacco smokers reported changes in taste, e-cigarette users did not. Reporting gingival inflammation with use of tobacco and e-cigarettes agrees with prior studies showing this association [ 29 , 30 , 31 , 32 , 33 ]. Smoking masks gingival inflammation by reducing gingival bleeding due to the vaso-constrictive effects of nicotine and lower hemorrhagic responsiveness in smokers [ 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have evaluated the impact of vaping on the management of periodontal disease compared with conventional cigarette smokers and non-smokers. Results of the studies focusing on changes in clinical periodontal parameters, inflammatory mediators and periodontopathic microflora suggest the following three mechanisms regarding how vaping affects the periodontium: impaired immune and inflammatory response, a shift in micro flora favoring periodontal pathogens, and subsequent changes in the healing capacity of soft tissue [ 24 , 39 , 44 ]. These mechanisms are similar to the deleterious effects of conventional smoking.…”
Section: Discussionmentioning
confidence: 99%
“…suggest the following three mechanisms regarding how vaping affects the periodontium: impaired immune and inflammatory response, a shift in micro flora favoring periodontal pathogens, and subsequent changes in the healing capacity of soft tissue [24,39,44]. These mechanisms are similar to the deleterious effects of conventional smoking.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported that, over time, EC smoking may change the bacterial makeup of saliva in a manner similar to that of cigarette smoking, which could increase the relative abundance of pathogens linked to periodontal disease. EC use has also been linked with increased levels of proinflammatory cytokines, such as tumor necrosis factor alpha (TNF-α) and interferon gamma (IFN-γ), exacerbating disease states [ 71 ]. Mohajeri et al also reported on the relationship between EC usage and periodontal health among the US adult population.…”
Section: Reviewmentioning
confidence: 99%